Clinical efficacy of percutaneous nephrolithotomy versus retrograde intrarenal surgery for pediatric kidney urolithiasis: A PRISMA-compliant article. Issue 43 (October 2017) - Lu, Pei; Song, Rijin; Yu, Yuzhou; Yang, Jie; Qi, Kai; Tao, Rongzhen; Chen, Keliang; Zhang, Wei; Gu, Min
Abstract: Background: Percutaneous nephrolithotomy (PCNL) and retrograde intrarenal surgery (RIRS) are widely used for pediatric upper tract stones; however, comparisons of their clinical efficacies are needed. Methods: Literature searches for relevant articles were performed using PubMed, the Cochrane Central Register of Controlled Trials, Embase and the China CNKI database. Study quality was assessed by Jadad and Newcastle–Ottawa Scales. Standard mean differences (SMDs) or odds ratios (OR), and 95% confidential intervals (95% CIs) were pooled for meta-analysis. In addition, data was evaluated the quality of the body of evidence by means of grading of recommendations assessment, development, and evaluation (GRADE). Results: Data from 4 studies (231 PCNL, 212 RIRS cases) were analyzed. There was no significant difference in operation time (SMD: 1.39; 95% CIs: −0.049 to 2.82; P  = .058), overall stone-free rate (OR: 3.72; 95% CIs: 0.55–25.22; P  = .18), or complication rate (OR: 1.92; 95% CIs: 0.90–4.07; P  = .091). PCNL cases had longer hospital stays (SMD: 1.22; 95% CIs: 0.95–1.50; P  < .001), but showed a higher stone-free rate for stones greater than 20 mm (OR: 6.38; 95% CIs: 1.83–22.22; P  = .004). For stones less than 20 mm, however, no significant difference between PCNL and RIRS was found (OR: 0.92; 95% CIs: 0.33–2.55; P  = .87). The quality of evidence based on the GRADE system was low. Conclusion: Results of our systematic review and meta-analysis suggest that, for the treatment of larger kidney stones (>20 mm) in pediatric patients, PCNL is a better option due to its higher stone-free rate, although RIRS may be associated with shorter hospital stays. A large-scale clinical trial is necessary to validate our findings. Abstract : Supplemental Digital Content is available in the text